Orientasi Kewirausahaan dalam Meningkatkan Kinerja Bisnis - Nandha Narendra Muvano; Achmad Helmy Djawahir; Rofiaty Rofiaty (Jurnal Bisnis dan Manajemen, 2018)
The purpose of this research is to know and describe the process of the orientation component of entrepreneurship (Passion, Risk Taking, proactive, innovative) in improving business performance by Siti Hajnia as Owner of Saboten Shokudo as an individual culinary business owner in Malang. The research method used in this research is qualitative research method of phenomenology. Data analysis technique used in this research is with interactive model. The results showed that the role of Orientation Entrepreneurship in improving business performance in accordance between the theory with the circumstances that occur in the field that includes a passion and Risk-taking DOI : https://doi.org/10.26905/jbm.v5i1.2314